Pengaruh customer relationship management terhadap customer satisfaction Starbucks di wilayah Bandung - Annahli, Yuliarti Maghfira; Piyoh, Dea Dela; Gaffar, Vanessa (Entrepreneurship Bisnis Manajemen Akuntansi (E-BISMA), 2024)
One of the coffee beverage brands that has been named as a company that is able to provide the best service for consumers, but in terms of what kind of service and how is provided by Starbucks so that it can provide satisfaction for consumers with its products and can be named the company with the best service in its field. On that basis, this study aims to determine and analyze how customer relationship management affects customer satisfaction at Starbucks in the Bandung area. This research is a quantitative study with explanatory survey research techniques. The population of this research is Starbucks consumers with a sample of 100 respondents through non-probability sampling technique purposive sampling method. This research data collection is in the form of distributing questionnaires to buyers of Starbucks products. The data analysis technique used is descriptive analysis and inferential analysis, which is assisted by the Partial Least Square (PLS) 4.0 analysis tool. The results of this study on customer relationship management variables have a significant effect on customer satisfaction.